2021
DOI: 10.1186/s12887-021-02503-8
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of methods for assessment of sex differentials in early childhood mortality

Abstract: Background While assessment of sex differentials in child mortality is straightforward, their interpretation must consider that, in the absence of gender bias, boys are more likely to die than girls. The expected differences are also influenced by levels and causes of death. However, there is no standard approach for determining expected sex differences. Methods We performed a scoping review of studies on sex differentials in under-five mortality, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 118 publications
1
2
0
Order By: Relevance
“…This aligned with the results of a previous study in Bangladesh (Karra et al, 2017;Khan & Awan, 2017). This research demonstrated that boys had a higher risk of death than girls, and these findings aligned with previous studies in Africa, including Nigeria, and Indonesia (Adebowale et al, 2020;Costa & Victora, 2021;dewuyi et al, 2016;Titaley et al, 2008). Boys are genetically and biologically weaker and more susceptible to contracting infectious diseases than girls (Muenchhoff & Goulder, 2014), such as congenital malformations of the urogenital system (Nair et al, 2013) and acute lung respiratory infection (Antehunegn & Worku, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…This aligned with the results of a previous study in Bangladesh (Karra et al, 2017;Khan & Awan, 2017). This research demonstrated that boys had a higher risk of death than girls, and these findings aligned with previous studies in Africa, including Nigeria, and Indonesia (Adebowale et al, 2020;Costa & Victora, 2021;dewuyi et al, 2016;Titaley et al, 2008). Boys are genetically and biologically weaker and more susceptible to contracting infectious diseases than girls (Muenchhoff & Goulder, 2014), such as congenital malformations of the urogenital system (Nair et al, 2013) and acute lung respiratory infection (Antehunegn & Worku, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…10,12 A prior analysis found that the Hadlock standard was twice as likely to consider female fetuses as being <10 th percentile compared with male fetuses, even though female fetuses had significantly lower morbidity than male fetuses. 14,15 Population fetal growth standards that do not account for fetal sex, such as the Hadlock standard, may generate disparities in diagnoses of abnormal growth between fetal sexes that may not be justified by morbidity. Given the knowledge of sex differences in fetal growth and the routine prenatal assessment of fetal genitalia, 1 the lack of investigation into sex-specific intrauterine growth standards represents an important gap in both research and clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…After early infancy, however, girls do not show the same advantages in survival due to infectious diseases; thus, sex differentials in child mortality tend to be lower than those of infant mortality, with those of under-five mortality taking values between the two [3]. Excess female mortality could indicate the presence of factors outweighing the expected biological survivorship conferred on girls during these ages, as would occur if girls are subjected to unequal access to healthcare, nutrition, or sex-related biases because of community preference for males [4]. On the other hand, higher-than-expected sex mortality ratios, indicative of inequities against male children, might point to a change in mortality to an extent greater than biologically expected.…”
Section: Introductionmentioning
confidence: 99%